HUBUNGAN TINGKAT STRES, AKTIVITAS FISIK, DAN DURASI TIDUR TERHADAP IMT MAHASISWA PROGRAM STUDI GIZI UPN VETERAN JAKARTA DIMASA PANDEMI COVID-19 - Ratu Aulia (2022)
Body Mass Index (BMI) is a measure to show nutritional status in adults. There are several factors that affect body mass index, namely stress levels, physical activity, and sleep duration. Stress levels, physical activity, and sleep duration can affect BMI with changes in appetite and daily activity habits. The purpose of this study was to determine the relationship between stress levels, physical activity, and sleep duration on the BMI of nutrition students at UPN Veteran Jakarta during the COVID-19 pandemic. This study used a cross sectional study design with sampling using purposive sampling technique. The number of respondents was 75 respondents. Data was collected by distributing questionnaires and anthropometric measurements. Analysis of the data used is the chi square test because the data are not normally distributed and each variable uses ordinal (categorical) scale data. Based on the results of statistical tests, it shows that there is no relationship between stress levels, physical activity, and sleep duration on BMI of nutrition students during the COVID-19 pandemic with each p-value of 1.00 on stress levels; 0.723 on physical activity; and 0.570 on sleep duration.